A new test apparatus to measure the adhesive shear strength of impact ice on titanium 6Al-4V alloy - Pervier, Marie Laure A.; Gurrutxaga Lerma, B.; Piles Moncholi, Eduardo; Hammond, David W. (Elsevier, 2019)
We present a new shear test which may be used in an icing environment. Ice is formed on a jig containing the sample material and this is then loaded by a forcing mechanism to effect the adhesive test. It allows impact (atmospheric) ice adhesive shear tests to be undertaken without disturbance or delay, in icing conditions. Finite element analysis is used in order to evaluate the controlling shear stresses in the most highly stressed zone of the ice/substrate interface and some sample experimental data is given for the adhesion of some impact ices to Ti-6Al-4V alloy with different surface finishes. The adhesion forces reported, represent peak values rather than spatially averaged stress values. Therefore values of adhesive shear strength obtained are higher than previous authors (in the range from 2 to 14 MPa instead of 0.05 to 0.5 MPa).
Keywords: Atmospheric ice; Impact ice; Finite element analysis; Shear strength; Fracture mechanics